Penentuan Kadar Senyawa Flavonoid Ekstrak Etanol Daun Kunyit (Curcuma domestica Val) Secara Spektrofotometri Uv-Vis - Mahral Effendi S (Program Studi S1 Farmasi, STIKES Senior, Medan, 2019)
A study concerning the determination level total of flavonoid and phenolic of White Tumeric Rhizoma Extract. The purpose of this study was to determine the levels total, flavonoids and phenolics of White Tumeric Rhizoma Extract. Extraction of chemical constituents of White Tumeric Rhizoma Extract performed by maceration method using methanol until the filtrate was clear. Determination level total of flavonoid and phenolic was conducted using spectrophotometry UV-Vis. Total flavonoid was tested using a quercetin standard and total phenolic content was tested using standard gallic acid. The results were obtained with concentrations of total flavonoid is 4,8%.